The Value of Muscle Thickness of Lower Limbs in Detection of Diabetic Peripheral Neuropathy - Abdulkareem, Sally H.; Ameer, Abdulnasir H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Neuropathy stands out as the highest-prevalence diabetes-related complication, impacting no less than 50% of individuals with diabetes throughout their lifespan. As the most common reason for disability due to walking difficulties, foot ulcerations, and limb loss, diabetic peripheral neuropathy is worthy of study, and early diagnosis of its signs is required. Objectives: This study aims to aid in the identification of diabetic peripheral neuropathy by determining the muscle thickness of the lower extremities in patients with diabetes mellitus. Methods: The study included 24 subjects with diabetic peripheral neuropathy and 25 individuals as a control group, subdivided into 10 diabetic patients without diabetic peripheral neuropathy and 15 healthy individuals. Both control and case subjects underwent peroneal and tibial motor nerve conduction studies, and high-resolution muscle ultrasounds to measure muscle thickness. The abductor hallucis muscle, extensor digitorum brevis muscle, extensor hallucis longus muscle, tibialis anterior muscle, and rectus femoris muscle were evaluated using ultrasound. Results: Comparing the tested muscles in diabetic patients with diabetic peripheral neuropathy to the control groups, the study revealed a statistically significant decrease in the thickness of many of the muscles being tested. Conclusions: These findings suggest that quantitative muscle ultrasound could be beneficial in identifying muscle changes associated with diabetic peripheral neuropathy. However, additional studies are necessary to verify the results in larger samples of diabetic patients.